Systemic delivery of biotherapeutic RNA to the myocardium transiently modulates cardiac contractility in vivo - Vladimir V. Shuvaev; Ying K. Tam; Benjamin W. Lee; Jacob W. Myerson; Alan Herbst; Raisa Yu. Kiseleva; Patrick M. Glassman; Hamideh Parhiz; Mohamad-Gabriel Alameh; Norbert Pardi; Hiromi Muramatsu; Tea I. Shuvaeva; et al. (Proceedings of the National Academy of Sciences, 2025)
Lipid nanoparticles (LNP) represent a versatile platform for improving delivery of therapeutic nucleic acids. Yet, delivery to the myocardium remains a formidable challenge due to local barriers in the heart and systemic hindrances. In particular, plasma apolipoprotein E (apoE) directs LNP to the liver, limiting potential extrahepatic delivery. Here, we report a cardiotropic LNP (cLNP), which within 30 min post–intravenous injection accumulates in the heart of ApoE knockout ( Apoe −/− ) mice. The findings were confirmed for Apoe −/− rats and for wild-type mice after siRNA-mediated plasma apoE ablation. To test cardiac-specific functional effects as a proof of concept, we used cLNP loaded with siRNA to ATP2A2, encoding the sarcoplasmic-endoplasmic reticulum Ca 2+ ATPase 2a (SERCA2A). This cardiomyocyte-specific protein is a key regulator of contractility and relaxation. Intravenous administration of cLNP/siRNA-ATP2A2 in Apoe −/− mice led to near-complete ablation of SERCA2A in the myocardium and a potent modulation of contractility of the cardiomyocytes obtained from these mice. In summary, cardiotropic nanocarriers may allow the delivery and effect of RNA and other agents to the myocardium. Achieving this unmet medical need promises new types of treatment for heart diseases, which remains the leading cause of death worldwide.